PERANCANGAN SISTEM INFORMASI PENGELOLAAN DANA BOS (BANTUAN OPERASIONAL SEKOLAH) PADA SMA WARGA SURAKARTA - Firdhaus Hari Saputra Al Haris; Dahlan Susilo; Budi Prabowo (Universitas Sahid Surakarta, 2014)
Reporting information system operational assistance funds in the creation of the school reports are still using manual systems resulting in many poses problems ofslowness in making such report Fund boss.The purpose of this research is to address existing problems as well as facilitate the school in the making of the management of the operational grant school by using an application that is designed. The research method used is field research, interviews and research librarianship. Types of data collected primary datawere obtained from the results of the interviews and observation. The selected software methodology is the waterfall methodology. The stages being performed are: analysis of system design diagrams, DFD, ERD and context isthen implemented through the programming language Visual Basic 8.0 and MySql as a database. The results of this research in the form of software applications thatcan be used by TBS and is able to present information accurately BOSS fund reporting.